Different Effects of Word Concreteness in a Recall and Recognition Task - Lujić, Anja; Vasović, Senka; Janković, Marko; Popović Stijačić, Milica; Mićunović, Dunja (24th Psychology Days in Zadar: Book of Selected Proceedings, 2026)
Based on Dual Coding Theory, Depth of Processing Theory, and Perceptual Symbols Systems Theory, we examined the relationship between the concreteness effect and depth of processing in memory tasks. We also manipulated the number of sensory modalities associated with concrete words to test the peg hypothesis, which suggests that additional sensory cues enhance recall. The participants were randomly assigned to one of three semantic rating tasks—concreteness, context availability, or vividness—and rated words accordingly. The words were categorised as abstract, few-modalities, or many-modalities based on the number of sensory experiences they evoke. After completing the rating task, all the participants proceeded to a mental rotation task, followed by random assignment to one of three previously unannounced memory tasks: free recall, cued recall, or recognition. As expected, the vividness group achieved the highest retrieval across all tasks, while the other groups showed no clear pattern. Notably, abstract words were recalled most accurately in the cued recall task, while many-modality concrete words led to the highest recognition accuracy. These findings are discussed using the Dynamic Visual Noise Paradigm, as the mental rotation task may have interfered with the visualisation processes involved in consolidating concrete word representations. Our results do not support the peg hypothesis or the assumptions of Perceptual Symbols Systems Theory since no recognition difference was found between few- and many-modality concrete words.